2012
DOI: 10.1105/tpc.111.093575
|View full text |Cite
|
Sign up to set email alerts
|

POM-POM2/CELLULOSE SYNTHASE INTERACTING1 Is Essential for the Functional Association of Cellulose Synthase and Microtubules inArabidopsis   

Abstract: In plants, regulation of cellulose synthesis is fundamental for morphogenesis and plant growth. Cellulose is synthesized at the plasma membrane, and the orientation of synthesis is guided by cortical microtubules; however, the guiding mechanism is currently unknown. We show that the conditional root elongation pom2 mutants are impaired in cell elongation, fertility, and microtubule-related functions. Map-based cloning of the POM-POM2 locus revealed that it is allelic to CELLULOSE SYNTHASE INTERACTING1 (CSI1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
272
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(287 citation statements)
references
References 61 publications
11
272
0
4
Order By: Relevance
“…We made longitudinal sections of the first internodes allowing structural characterization of intact and transected xylem vessels in the previously described csi1/pom2 mutants pom2-4 and csi1-1/pom2-8 (Bringmann et al, 2012) as well as wild-type plants ( Figures 1A and 1B). We found that the secondary wall bands were significantly more disordered in the pom2-4 and csi1-1/pom2-8 mutants, as evident from measuring the spread in orientation angles of neighboring wall bands ( Figure 1C).…”
Section: Csi1/pom2 Influences Xylem Vessel Wall Patterningmentioning
confidence: 99%
See 2 more Smart Citations
“…We made longitudinal sections of the first internodes allowing structural characterization of intact and transected xylem vessels in the previously described csi1/pom2 mutants pom2-4 and csi1-1/pom2-8 (Bringmann et al, 2012) as well as wild-type plants ( Figures 1A and 1B). We found that the secondary wall bands were significantly more disordered in the pom2-4 and csi1-1/pom2-8 mutants, as evident from measuring the spread in orientation angles of neighboring wall bands ( Figure 1C).…”
Section: Csi1/pom2 Influences Xylem Vessel Wall Patterningmentioning
confidence: 99%
“…The primary wall CSCs typically track with a speed of ;250 nm/min (Paredez et al, 2006), and CSI1/POM2 proteins track together with these CSCs (Bringmann et al, 2012). However, the secondary wall CSCs track significantly faster than the primary wall CSCs (Watanabe et al, 2015), and if the CSI1/POM2 proteins are associated with the secondary wall CSCs, one would anticipate an increase in speed of the CSI1/POM2s over time after VND7 induction.…”
Section: Csi1/pom2 Mimics the Behavior Of And Can Interact With Thementioning
confidence: 99%
See 1 more Smart Citation
“…Reduced CESA Velocity after Indaziflam Treatment Is CSI1 Independent CSI1 was identified as a primary linker protein between MTs and CSCs (Gu et al, 2010;Bringmann et al, 2012;Lei et al, 2012;Li et al, 2012). In csi1 mutants, CESA particles in the PM were found to display reduced velocity and their association with MTs was completely disrupted (Gu et al, 2010;Li et al, 2012).…”
Section: Isoxaben-and Quinoxyphen-resistant Plants Are Not Cross Resimentioning
confidence: 99%
“…The movement and insertion of cellulose synthase complexes in the plasma membrane is guided by the microtubule network attached to the cytoplasmic side of the plasma membrane during primary cell wall deposition [38][39][40] . The mechanism of the interaction between the microtubule array and cellulose synthase complexes is further elucidated by the discovery of the suggested scaffold protein POM2/CSI1 between cellulose synthase complexes and microtubules 112 . Besides guiding cellulose microfibril synthesis, the microtubule cytoskeleton is also involved in delivery of cell wall matrix material 113,114 .…”
Section: Regulation Of Primary Cell Wall Deposition By Plant Cellsmentioning
confidence: 99%